Die Allgemeine Erklärung der Menschenrechte: eine grundlegende Antwort auf historisches Unrecht - Krennerich, Michael; Huhle, Rainer (2008)

Fate and whereabouts: The two elements that make up the right to know about the victims of forced disappearance - Huhle, Rainer (Taylor and Francis, 2022)
When in the 1970s victims of what today is named ‘(en)forced disappearance’ began to struggle with this terrible form of state repression, especially in the Southern Cone, this struggle had two principal claims and aims: finding the disappeared persons and holding the perpetrators of the crime accountable. Already the first attempts to cast the new concept of ‘(en)forced disappearance’ into legal terms reflected these two aims, often in the twin formulae of demanding to investigate or clarify the ‘fate’ and the ‘whereabouts’ of the disappeared. While legal texts dedicate much effort to defining precisely the legal obligations to investigate the crime (the fate of the disappeared person), the duty to locate the disappeared person (to clarify the whereabouts) has been much less developed. The adoption in 2019 of the ‘Guiding Principles for the Search of Disappeared Persons’ by the UN Committee on Enforced Disappearance seeks to give the right to be searched for its due place in this relationship. This article traces the complex relationship between the right and the duty to search and the obligations to investigate throughout the history of the terms ‘fate’ and ‘whereabouts’ as used in the legal and political language dealing with ‘(en)forced disappearance’.
CRIS-Team Scopus Importer:2022-10-14